Men and depression : clinical and empirical perspectives - Cochran, Sam Victor, 1950- (Practical resources for the mental health professional., 2000)
Men and Depression: Clinical and Empirical Perspectives is the only book currently available that integrates psychological theories and the latest research findings with clinical recommendations for working with men who are suffering from depression. This volume covers a wide range of topics and issues that relate to men and depression, including: assessment of male depression; statistics on depression in men; theories to explain depression in men; treating depression in men with both pharmacotherapy and psychotherapy; the interrelation of grief, loss, trauma, and depression in men; the problem of suicide and how to assess and treat suicide risk in men; and prospects for future work in this important area. This is a unique reference and practical guide that integrates and evaluates research and clinical practice relating to the diagnosis and treatment of men with depression. The volume explores why men are underdiagnosed and undertreated for mood disorders and provides the clinician with practical guidelines for conceptualizing a treatment plan for men with depression. Key Features * Only book on the current market to address the complex nature of male depression * Integrates the latest research findings and clinical innovations * Offers guidelines for the assessment, diagnosis, and treatment of male depression * Addresses pharmacological treatments and their implications * Extensively illustrated with case material and clinical inquiries.